PEMIKIRAN SATIRA DALAM SASTERA DAKWAH DI MALAYSIA: SATU PERBAHASAN KONSEP - Mohd Zabidi, Ahmad Zahiruddin (JURNAL MELAYU SEDUNIA, 2020)
Studies in the field of dakwah writing in Malaysia are intensifying after the emergence of the work of Nor Raudah Hj. Siren (2013) Retorik Penulisan Dakwah (Rhetoric of Dakwah Writing), this manuscript comes from his PhD thesis. Apart from rhetoric, among the genres that are not given widespread attention is satire, whether in general writing or fiction. Research on satire specifically in the field of literature initiated by Fatimah Busu (1992) with the title Ciri-ciri Satira dalam Novel Melayu dan Afrika Moden: Kajian Perbandingan (The characteristics of Satire in Modern Novel Indonesia and Africa: A Comparative Study), followed by S. Othman Kelantan (1997) titled Pemikiran Satira dalam Novel Melayu (Satirical Thought in Malay Novels). Although Fatimah Busu and S. Othman Kelantan each study the subject of satire, but S. Othman Kelantan specializes in aspects of satire thought. A combination of the three sources above, the researcher deductively presents the concept of ‘Satire Thought in Da‘wah Literature Writing’.